Towards rich motion skills with the lightweight quadruped robot Serval. (June 2020) - Eckert, Peter; Schmerbauch, Anja EM; Horvat, Tomislav; Söhnel, Katja; Fischer, Martin S; Witte, Hartmut; Ijspeert, Auke J
Bio-inspired robotic designs introducing and benefiting from morphological aspects present in animals allowed the generation of fast, robust, and energy-efficient locomotion. We used engineering tools and interdisciplinary knowledge transferred from biology to build low-cost robots, able to achieve a certain level of versatility. Serval, a compliant quadruped robot with actuated spine and high range of motion in all joints, was developed to address the question of what mechatronic complexity is needed to achieve rich motion skills. In our experiments, the robot presented a high level of versatility (number of skills) at medium speed, with a minimal control effort and, in this article, no usage of its spine. Implementing a basic kinematics-duplication from dogs, we found strengths to emphasize, weaknesses to correct, and made Serval ready for future attempts to achieve more agile locomotion. In particular, we investigated the following skills: walk, trot, gallop, bound (crouched), sidestep, turn with a radius, ascend slopes including flat ground transition, perform single and double step-downs, fall, trot over bumpy terrain, lie/sit down, and stand up.